Watching English Native Speakers’ Youtube Channel to Improve Students’ Pronunciation Ability - Hasanah, Maufiratul; Wahono, Suparwoto Sapto (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2022)
Pronunciation is the way a letter, word, or language is spoken. It involves how a speaker produces sounds, stress, rhythm, and intonation in speech. Some English learners have difficulty with pronunciation since English is considered to be a foreign language in Indonesia. This research aims to show that watching English native speakers’ YouTube channel can improve students’ pronunciation ability. The researcher applied Classroom Action Research and it needed two cycles (four meetings). The criteria of success were that the students achieve the minimum standard or average score, which was equal to or greater than 70%. The students’ pretest score was 35% (very poor) and the result of the interview with the English teacher suggested that the students could not pronounce accurately since they rarely practice and never learn from native speakers. The first posttest score was 57,5% (very poor). The second posttest score was 87% (very good). It showed that the students’ score was increase and achieve the minimum standard. It could be concluded that watching English native speakers’ YouTube channel is an effective way to improve the students’ pronunciation ability.